2022
DOI: 10.1007/s00436-022-07477-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of a droplet digital polymerase chain reaction tool for the detection of Toxoplasma gondii in meat samples

Abstract: Toxoplasmosis is a zoonotic disease caused by the protozoan parasite Toxoplasma gondii. Infection in humans has usually been related to the consumption of raw, undercooked or cured meat. The aim of this study was to develop a droplet digital polymerase chain reaction (ddPCR)-based assay for the detection and quantification of T. gondii in meat samples. To optimize the ddPCR, T.gondii reference DNA aliquots at five known concentrations: 8000 cg/µl, 800 cg/µl, 80 cg/µl, 8 cg/µl were used. Moreover, results obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…When comparing the ddPCR and qPCR results, it was found that the latter underestimated the exposure pressure. Similarly, a uniplex Toxoplasma gondii detection assay performed better than qPCR when testing the diaphragm tissue samples from farm animals [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…When comparing the ddPCR and qPCR results, it was found that the latter underestimated the exposure pressure. Similarly, a uniplex Toxoplasma gondii detection assay performed better than qPCR when testing the diaphragm tissue samples from farm animals [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…ddPCR outperformed qPCR in identifying pathogen DNA in E. coli , C. jejuni , CMV , C. trachomatis , Salmonella, and HIV [ 23 , 24 , 25 , 26 , 27 ]. In the case of parasites such as Plasmodium , ddPCR was shown to be more sensitive and accurate than qPCR; however, in Toxoplasma, Cryptosporidium, Leishmania , Trypanosoma , Theileria equi, Theileria cervi , Babesia, Bartonella , and Borrelia species, ddPCR was found to be equivalent to qPCR [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Developing an assay with higher performance at low doses without the requirement for a reference standard curve should increase the detection of infection, hence facilitating case identification and disease monitoring. ddPCR is a breakthrough DNA quantification technique that avoids dependence on the reference standard curve and is effective in diagnosing and quantifying various human and animal pathogens, including vector-borne infections [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. With more consistent findings across technical replicates and higher sensitivity than qPCR, ddPCR has been gaining traction as a viable pathogen identification and quantification option.…”
Section: Introductionmentioning
confidence: 99%
“…The use of undercooked/raw meat with viable tissue cysts (Plaza et al 2020;Mancusi et al 2023) is thought to be a significant cause of infection due to T. gondii's propensity to spread to a wide range of animals and remain in their structures for years (Tenter et al 2000;Kuruca et al 2023). Human toxoplasmosis has been documented following the intake of raw and uncooked flesh and organs, and live parasites have been identified from fresh, frozen, and cured meat (Liu et al 2015;Kuruca et al 2023).…”
Section: Transmission Of T Gondii With Different Kinds Of Meatmentioning
confidence: 99%